Judgements on History and Historians - Burckhardt, Jacob, 1818-1897. (London ; New York : Routledge, 2007)
Ambitious in its scope, ranging from the days of Ancient Egypt, through the Reformation to the time of Napoleon, this title presents a history of Western Civilization.
Includes bibliographical references and index.
Translated from the German.
Keywords: World history